Lithium and Potassium Complexes with dbn- and dbu-Based Enamido Phosphine Ligands: Syntheses and Applications - Langer, Jens; Grams, Samuel; Puchta, Ralph (European Journal of Inorganic Chemistry, 2017)
The phosphines 6-diphenylphosphino-1,8-diazabicyclo[5.4.0]undec-7-ene (dbuPH) and 7-diphenylposphino-1,5-diazabicyclo[4.3.0]non-5-ene (dbnPH), containing amidine subunits, were successfully deprotonated by n-butyllithium or benzylpotassium. In the presence of Et2O or THF, the well-defined complexes [Li(dbnP)(Et2O)2] (1), [Li(dbuP)(Et2O)2] (2), [K(dbnP)(THF)∞] (3b) and [K(dbuP)(THF)22] (4) were obtained, while in the absence of such donors, polymeric [K(dbnP)∞] (3a) was formed. These alkali-metal derivatives are useful precursors for salt-metathesis reactions, and they allow the transfer of the enamido phosphine ligands to appropriate transition metals, as demonstrated by the syntheses of the new rhodium complexes [Rh(dbnP)(cod)] (5) and [Rh(dbuP)(cod)] (6). The reaction of 1 and 2 with Ph2PCl underlined the ambident character of dbnP– and dbuP– as nucleophiles and led to the new diphosphines dbn(PPh2)2 (two isomers C-7 and N-7) and dbu(PPh2)2 (N-8), in which either the carbon or the nitrogen atom of the former enamido moiety was substituted.
CRIS-Team Scopus Importer:2026-01-22
Keywords: Ambident nucleophiles; Hybrid ligands; Lithium; Potassium; Rhodium